Characterizing small RNA cargoes of exosomes from Diabrotica undecimpunctata (Coleoptera: Chrysomelidae) - Featherston, Kyah (Kansas State University, 2022)
Exosomes are extracellular communication vesicles utilized in both mammalian and insect systems. Most exosomal research to date has been conducted in mammalian systems, specifically in the field of biomedical research due to their ability to carry protein and RNA cargoes in both short- and long-range signaling pathways within an organism. In mammalian research, exosomes are important as both diagnostic mechanisms for detecting cancer and potentially other diseases, but also as vehicles for carrying therapeutic molecules throughout the body, including across the blood brain barrier. In insects, much less is known about exosomes. Previous studies have shown that exosomes play important roles in diverse aspects of insect biology and physiology, including in maintaining signaling gradients or carrying cargoes in developing embryo, in altering female mating behavior by enhancing egg laying and reducing mating receptivity, and in enhancing pathogen transmission to and from their insect vectors. More recently, evidence also suggests that exosomes may play a role in systemically spreading RNA interference (RNAi) responses within insects. However, there is a lack of information on the specific composition and cargoes that are carried by exosomes in insect systems. Such basic information is vital to understanding the roles that exosomes play in insect biology and physiology, as well as understanding how exosome-based signaling changes following stimulation. In this study, small RNAseq was conducted on exosomal RNAs isolated from cultured Diabrotica undecimpunctata cells (southern corn rootworm, SCR). The cells were either untreated or treated with double-stranded RNA (dsRNA) specific to a non-target gene (enhanced green fluorescence protein, EGFP) to determine how exosome cargoes change according to changing physiological conditions. Sequencing yielded over 10 million and 12 million reads, respectively, and small RNA reads from both sets of data showed a multimodal size distribution with main peaks at 28, 21-22, and 32 nt. Subsequent analysis identified miRNAs from the read data for each sample. Many miRNAs detected from SCR exosomes were homologous to miRNAs from the well characterized beetle, Tribolium castaneum, but unique miRNA sequences (912 unique miRNAs overall,616 of these were found in the control samples and 557 from the dsEGFP treated samples) were also predicted from the sequencing data. The miRNAs were compiled together and named in order of abundance, and isomiRNAs were detected and classified for naming with 812 unique sequences and 98 various isomiRNAs. No significant differences in the miRNA profiles were observed between treated and untreated samples; however, analysis of the small RNA reads from exosome RNA from dsEGFP-treated cells were also mapped to the EGFP gene sequence. This study shows that exosomes from SCR cells carried RNA cargoes in both untreated and dsRNA-treated systems, and that exosomes may contribute to spreading RNAi signals by carrying small RNA sequences corresponding to the dsRNA that was used for treating the parent cells. These results provide a firm foundation to continue characterizing insect exosomes and the roles that they play in insect biology and physiology. Future experiments will enhance these findings by also analyzing mRNA and protein cargoes carried by SCR exosomes and correlating our in vitro results with in vivo experiments. Subsequent experiments may also explore the biosynthetic pathways that produce exosomes in insects and the roles of specific miRNAs that are carried by exosomes.
Keywords: Exosome; Diabrotica undecimpunctata; miRNA